A comprehensive investigation on machining of composites by EDM for microfeatures and surface integrity. Issue 1 (May 2022) - Gudipudi, Suresh; Nagamuthu, Selvaraj; Subbian, Kanmani Subbu; Chilakalapalli, Surya Prakasa Rao
In electro-discharge machining (EDM), the material removal takes place by precisely controlled sparks that occur between tool and workpiece separated with a spark gap in the presence of a dielectric. Generally, the non-contacting type and less material removal rates are attributed to attain a good surface finish and close dimensional tolerances during an EDM of monolithic metals and alloys. But the dimensional accuracy and surface integrity parameters would considerably affect during EDM of composites due to the existence of more than one material phase constituents. Therefore, the present work aims to study and optimize the performance characteristics under various EDM conditions employed in making rectangular channels on AA6061-B4 C composite material. Initially, AA6061-4wt.%B4 C composites were fabricated by ultrasonically assisted stir-casting, and the improved properties were obtained from various mechanical characterizations. The EDM experiments were conducted according to the full factorial experimental design. The three levels of input conditions such as discharge Current (I), discharge duration (T On), and discharge idle time (T Off) were considered. The considered output responses are material removal rate (MRR), taper (θ) of the machined channel, tool wear rate (TWR), average surface roughness (R) of the machined surface, and average recast layer thickness (ARLT) of the machined zone. These responses are co-related with multi-objective types in the sense that the MRR has to be maximized with all other responses minimized. Hence, principal component analysis (PCA) coupled with grey relation analysis (GRA) was used for optimization in which the results were normalized, and all the responses were converted into a single response named weighted grey relation grade (WGRG) for each trial. The experimental trial, which had the highest WGRG, was considered as a local optimum. The global optimum parameters were obtained by performing the Taguchi method (TM) (higher-the-better) for the maximization of WGRG . The analysis of variance (ANOVA) was performed to know the contribution of each EDM parameter toward the WGRG . The optimum levels of Current, T On, and T Off were identified as 8 A, 25 µs, and 36 µs, respectively. Results showed that all three input parameters significantly affected the WGRG, and a higher contribution of Current (52.11%) followed by the T On (26.72%) was observed. The interaction between the Current and T Off was found to be greater than other interactions. Taper values were observed to be reduced at the combination of 8 A discharge Current and 25 µs T On . None of the input parameters significantly affected the R a, except for Current, which showed a slight effect. ARLT values showed an increasing trend of T On from 25 µs to 45 µs but decreased slightly at 65 µs for all Current levels. The moderate Current level 6 A was observed to be favorable in reducing ARLT when compared to low (4 A) and high (8 A) for all Ton values.